New Tax and Expenditure Elasticity Estimates for EU Budget Surveillance - Price, Robert (OECD Economics Department Working Papers, 2014)
This paper estimates the elasticities of government revenue and expenditure items with respect to the output gap for European Union (EU) countries. These elasticities are used by the European Commission, as part of the EU fiscal surveillance process, to calculate the semi-elasticity of the budget balance as a percentage of GDP with respect to the output gap. The study updates the earlier 2005 study of OECD economies using the most recent datasets and tax codes, the coverage being confined in this paper to the 28 EU member states, seven of which are not OECD members. The same basic two-step methodology is retained: revenue and expenditure elasticities with respect to the output gap being defined as the product of, first, the elasticities of individual revenue and expenditure items with respect to their bases and, second, the elasticities of these bases with respect to the output gap. A number of refinements and methodological improvements are made relative to the 2005 study. The revisions to individual elasticities relative to the 2005 vintage are significant in a number of cases but do not follow a clear pattern across countries, except for the elasticities of corporate income tax revenue which are revised up in most cases